ESTIMATES OF THE DURATION OF DEPLETION IN TIME OF THE LIQUID FLOW OF A RIVER IN THE ABSENCE OF PRECIPITATION BY ANALYZING THE DECAY CURVE OF THE FLOW HYDROGRAPH (PANGEEA, 2026)
Under the current climate change and due to the fact that water resources are limited and under increasing pressure, it is necessary to analyze the problems encountered during periods of scarcity. An analysis of the downward curve of the hydrograph of streamflow through the behavior of a watershed in the absence of precipitation will determine a forecast of the runoff through rivers. The decline in the flow of a river during periods of low or no precipitation is reflected as a downward curve and defines the drainage or rate of decline. For the planning and management of water resources, as the main source of water supply for Vaslui municipality and adjacent areas is the Solesti reservoir, it is necessary to analyze the downward curve of the hydrograph of the river upstream of the reservoir, the way in which certain processes and groundwater resources re-draw the runoff in the riverbed during dry periods.